Do Risk Factors for Incapacitated and Other Sexual Assault Differ for Black and White College Women? A Preliminary Investigation - Wiseblatt, Aria F. (Violence against women, 2025)
Heavy episodic drinking (HED) and hookups are risk factors for college women's sexual assault (SA). Black women engage in these behaviors less frequently than White women. We prospectively examined HED and hookups as mechanisms of incapacitated SA (ISA) and other SA (OSA) risks for Black and White first-year college women and sociocontextual factors that may contribute differentially to risk. In mediation analyses, Black women's less frequent HED predicted lower ISA. SA characteristics (e.g., setting) also differed by race. Mechanisms and types of assault risk may not be the same for all college women, an important consideration for intervention efforts.